Case report: Regression of in-transit metastases of cutaneous squamous cell carcinoma with combination pembrolizumab and topical diphencyprone - Poplausky, Dina; Young, Jade N.; Block, Brandon R.; Estrada, Yeriel; Singer, Giselle K.; Wong, Vicky; Cabral, Patricia; Suemitsu, Yamato; Kim, Randie H.; Friedlander, Philip; Gulati, Nicholas (Frontiers in Oncology, 2024)
While typically low-risk, cutaneous squamous cell carcinoma (cSCC) can infrequently progress to metastatic disease with in-transit lesions, localized to the dermis or subcutaneous tissue between the primary tumor and draining regional lymph nodes. These lesions are associated with poor prognostic values, including decreased survival rates and increased risk of recurrence. We present the case of a 75-year-old male with cSCC and in-transit metastases on his scalp treated with the immune checkpoint inhibitor (ICI) pembrolizumab in conjunction with diphencyprone (DPCP), a topical hapten that induces a delayed-type hypersensitivity reaction in the skin. The patient was enrolled in a clinical trial (NCT05481658) that involved the twice-weekly application of DPCP 0.04% ointment to four of the in-transit metastases on his frontal scalp, concurrent with pembrolizumab 300 mg administered every three weeks. Following effective sensitization and a twelve-week treatment course, complete clearance of all lesions, DPCPtreated and non-DPCP treated, was achieved, with no adverse events. The immunologic profiles of the post-treatment biopsies were analyzed by TaqMan Low Density Array quantitative realtime polymerase chain reaction to measure immune marker gene expression. Relative to the non-DPCP-treated lesion, the DPCP-treated lesion demonstrated increased pro-inflammatory genetic markers and T-cell activation. This case represents the first reported instance of in-transit metastases of cSCC successfully treated with DPCP and an ICI. It highlights the potential safety and efficacy of DPCP with systemic immunotherapy for the management of in-transit metastases of cSCC in patients for whom surgery and radiation may be contraindicated.